BLANDED LEARNING DI ERA NEW NORMAL - Dyanti Mahrunnisya (Journal of Social Science Education, 2022)
Blended Learning is a learning innovation that combines technological advances in accordance with the demands of learning in the 21st century and is relevant to the learning transition period of offline to online learning, online to offline due to the covid-19 pandemic. This study aims to describe the implementation of blended learning learning. The method used in this research is the Systematic Literature Review (SLR), with a qualitative descriptive approach to the results of several studies with secondary data. Based on the results of the discussion, the application of blended learning is one solution that can be used in learning today by using various kinds of online applications, web, streaming, video, and so on.